Implementasi Kebijakan Pencegahan dan Penanggulangan Covid-19 Sebagai Bentuk Manuver Organisasi Dinas Kesehatan Provinsi Bali - Reditiya, I Dewa Dalem Siwa; Subanda, I Nyoman; Darma, Gede Sri (Majalah Ilmiah DIAN ILMU, 2023)
The Covid-19 pandemic has overhauled all structures of life, be it in the economic, social and cultural aspects. The Covid-19 virus is the government's main focus in preventing and tackling it so it doesn't spread and takes many victims. This study aims to analyze the implementation of policies from both the central and regional governments carried out by the Bali Provincial Health Office. This research is a qualitative research with data collection techniques, namely observation, documentation and interviews with 7 informants from the government, community and policy observers taken using purposive sampling technique and data analyzed by triangulation. The results of this study stated that overall the dimensions of good policy implementation according to Edward III, namely Communication, Resources and Bureaucratic Structure had been carried out well by the Bali Provincial Health Office in carrying out or carrying out regulations or rules regarding handling and preventing the Covid-19 pandemic. From other dimensions, according to Van meter Van horn, namely Standards and Policy Targets as well as Compliance and Executors' Responsiveness, it is considered sufficiently precise and accurate.